Factores biosocioculturales y su relación con la edad de inicio de las relaciones coitales en adolescentes 2011 - Bardales Beltran, Marujita (2011)
This research study, of type quantitative, descriptive and correlational was performed on Health Center “Victor Larco”, on Victor Larco District - 2011, in order to determine the relationship between biosocioculturals factors: sex, family structure, family functioning and social skills with age of onset of intercourse among adolescents. The sample universe was consisted of adolescents old who met the inclusion criteria of the investigation. For data collection was used the instrument: Factors associated with age at first intercourse in the teenager. The information obtained was processed in SPSS 15.0 version and analyzed by statistical test "chi square". The results are presented in tables of simple and double-entry, after analysis was obtained the following conclusions: 1. Of all the adolescents in the study, 54 percent are male, 52 percent have a nuclear family, 36 percent have a good family functioning and 36 percent have average social skills. 2. 36 percent of adolescents initiate sexual intercourse in early adolescence, with the same percentage that intermediate incidence in adolescence and 28 percent starting in late adolescence. 3. Sex, family functioning and social skills are the factors that relate biosocioculturales statistically significant with age of onset of intercourse among adolescents. 4. The family structure is the factor that is unrelated biosociocultural statistically significant with age of onset of intercourse among adolescents.